Strategi Guru Pendidikan Agama Islam Dalam Mengatasi Kenakalan Siswa SDN 03 Pakan Labuh - Putra, Romi; Puadi, Asral (Indonesian Research Journal on Education, 2023)
Meanwhile, some experts argue that child delinquency (Jumawati, S.Pd., M.Pd, 2021) is a failure to obtain a response that is socially acceptable or a failure to obtain a moral and ethical understanding that is appropriate tosocial culture. The reasons for this failure all stem from developmental issues. Child Psychology deals with the process of the child's superego moving towards appropriate and adequate socialization, which may also be caused by the inability to adapt to the general behavior of the surrounding community. The research here that researchers use is qualitative research or qualitative is a type of research that produces findings that cannot be achieved (Gunawan, 2022) using statistical procedures or other quantitative methods. According to Strauss and Corbin(2007:1), this qualitative research is research that can be used to study community life, history, behavior, organizational functionalization, social movement, or kinship relations. Findings from interviews, observations and documentation of violations by SD N03 Pakan Labuh students can find out the findings of the causes of studentdelinquency caused by factors such as the child himself and the family environment and social environment. the factors that cause student discipline violations come from the students themselves, such as not being able to control emotions, lack of self-discipline, being too lazy to do homework or homework, taking too long to dohomework given by the teacher, the PAI teacher's strategy in prohibiting values Moral education for children at SD N03 Pakan Labuh is direct learning and exemplary in the classroom. The PAI teacher's strategy to increase children's awareness of moral values at SD N03 Pakan Labua is a strategy that provides advice and habits. The PAI teacher's strategy in monitoring children's behavior at SD N03 Pakan Labuh is directsupervision.